A novel nanobody-based HER2-targeting antibody exhibits potent synergistic antitumor efficacy in trastuzumab-resistant cancer cells - Liu, Xinlin; Luan, Linli; Liu, Xi; Jiang, Dingwen; Deng, Junwen; Xu, Jiazhen; Yuan, Yang; Xing, Jiyao; Chen, Bingguan; Xing, Dongming; Huang, Haiming (Frontiers in Immunology, 2023)
Human epithelial growth factor receptor-2 (HER2) plays an oncogenic role in numerous tumors, including breast, gastric, and various other solid tumors. While anti-HER2 therapies are approved for the treatment of HER2-positive tumors, a necessity persists for creating novel HER2-targeted agents to resolve therapeutic resistance. Utilizing a synthetic nanobody library and affinity maturation, our study identified four anti-HER2 nanobodies that exhibited high affinity and specificity. These nanobodies recognized three distinct epitopes of HER2-ECD. Additionally, we constructed VHH-Fc and discovered that they facilitated superior internalization and showed moderate growth inhibition. Compared to the combination of trastuzumab and pertuzumab, the VHH-Fc combos or their combination with trastuzumab demonstrated greater or comparable antitumor activity in both ligand-independent and ligand-driven tumors. Most remarkably, A9B5-Fc, which targeted domain I of HER2-ECD, displayed significantly enhanced trastuzumabsynergistic antitumor efficacy compared to pertuzumab under trastuzumab-resistant conditions.Our findings offer anti-HER2 nanobodies with high affinity and non-overlapping epitope recognition. The novel nanobody-based HER2-targeted antibody, A9B5-Fc, binding to HER2-ECD I, mediates promising receptor internalization. It possesses the potential to serve as a potent synergistic partner with trastuzumab, contributing to overcoming acquired resistance.